Significant Reduction in Vaccine-Induced Antibody Levels and Neutralization Activity Among Healthcare Workers and Nursing Home Residents 6 Months Following Coronavirus Disease 2019 BNT162b2 mRNA Vaccination. (19th November 2021) - Canaday, David H; Oyebanji, Oladayo A; Keresztesy, Debbie; Payne, Michael; Wilk, Dennis; Carias, Lenore; Aung, Htin; St. Denis, Kerri; Lam, Evan C; Rowley, Christopher F; Berry, Sarah D; Cameron, Cheryl M; et al.
Abstract: Antibody decline occurred from 2 weeks to 6 months post-BNT162b2 mRNA vaccination in nursing home (NH) residents and healthcare workers. Antispike, receptor-binding domain, and neutralization levels dropped >81% irrespective of prior infection. Notably, 69% of infection-naive NH residents had neutralizing antibodies at or below the assay's limit of detection.